2012
DOI: 10.1007/s11999-011-2219-x
|View full text |Cite
|
Sign up to set email alerts
|

Coronal Plane Knee Moments Improve After Correcting External Tibial Torsion in Patients With Cerebral Palsy

Abstract: Background External tibial torsion causes an abnormal axis of joint motion relative to the line of progression with resultant abnormal coronal plane knee moments and affects lever arm function of the foot in power generation at the ankle. However, it is unclear whether surgical correction of the tibial torsion corrects the moments and power.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Accordingly, many researchers stress the necessity of proper lower-limb segmental alignment in the transverse plane for producing the internal plantar flexor moment that facilitates knee extension in single support, and improves the kinematic and kinetic gait deviations. 2628…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, many researchers stress the necessity of proper lower-limb segmental alignment in the transverse plane for producing the internal plantar flexor moment that facilitates knee extension in single support, and improves the kinematic and kinetic gait deviations. 2628…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, many researchers stress the necessity of proper lowerlimb segmental alignment in the transverse plane for producing the internal plantar flexor moment that facilitates knee extension in single support, and improves the kinematic and kinetic gait deviations. [26][27][28] A dynamic splinting is certainly a viable and useful physical therapy intervention tool for modulating biomechanical mal-alignment and poor postural control in children having cerebral palsy. Many researchers proposed that therapeutic strapping would provide the foundation for increasing proprioceptive and tactile awareness, restoring optimal muscle length to provide a basis for normal firing and recruitment patterns and orienting the muscle force along normal vectors in the frontal and sagittal planes.…”
Section: Variablementioning
confidence: 99%
“…The mechanical loading of an externally or internally deviated foot is atypical, and thus believed to be a contributing factor to progressive foot deformity (2). Finally, foot progression deviations can cause atypical loading of the knee joint in the coronal and transverse planes, which could, over time, hasten or worsen degenerative knee conditions such as osteoarthritis (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…In their study, they found that older age and higher GMFCS level were the most significant predictors for increased external tibial torsion. Thus, significant increases in external rotation at TMA and in tibial rotation during gait in the longer term after both MHL and MLHL are likely related to a trend present with growth in children with CP rather than directly related to the surgical intervention [34,45,46]. Similarly, in a study evaluating external tibial derotation osteotomies in children with spastic CP to address internal tibial rotation and crouch gait, there was a tendency for overcorrection of internal rotation at long-term follow-up [46].…”
Section: Discussionmentioning
confidence: 99%